Investigating the Effect of the Relationship between Brand Visual Identities, Focus on Employees and Customers and Brand Personality on Organizational Commitment - KHOSHBIN, SAEID REZA (The journal of contemporary issues in business and government, 2021)
Corporate brand identity is a key issue for any organization. Accordingly, its study is a profitable field of research. As a result, companies should pay special attention to brand identity management because it affects employees' commitment to the organization, their job satisfaction, and brand performance. The present study aimed to investigate the role of organizational commitment in the relationship between organizational brand identity, brand performance and job satisfaction of Shahr Bank employees. The present research is applied in terms of purpose and descriptive-correlational in terms of data collection. The statistical population of the study was the employees of Shahr Bank which was estimated to be 120 samples through Morgan table, and then the data were collected using cluster sampling method. A questionnaire was used to collect information, which was distributed among the sample after confirming its validity and reliability (Cronbach's alpha coefficient of 0.94%). Finally, after collecting data, the data were analyzed using structural equations (Smart PLS). To analyze the research data, two methods of descriptive statistics and inferential statistics have been used. The results show that brand identity has a positive effect on employee commitment, as well as sub-hypotheses of positive effect of focus on customer and employee, brand personality and having consistent relationships on the formation of brand identity were confirmed. Also positive effect of brand visual identity and human resource planning on the formation of brand identity was not confirmed according to the results. Finally, the hypotheses of a positive effect of employee commitment on brand performance and employee job satisfaction were confirmed.